Factors impacting effective altruism: revisiting heuristics and biases in charity in a replication and extension registered report of Baron and Szymanska (2011) - Mannix Chan; Gilad Feldman (Royal Society Open Science)
Individuals who donate to charity may be affected by various biases and donate inefficiently. In a replication and extension registered report with a US Amazon Mechanical Turk sample using CloudResearch (N = 1403), we replicated studies 1 to 4 in Baron & Szymanska (Baron & Szymanska 2011 In The science of giving: experimental approaches to the study of charity (eds DM Oppenheimer, CY Olivola), pp. 215–235 (doi:10.4324/9780203865972-24)) with extensions on reputation and overhead funding. We found support for the effects of a preference for lower perceived waste (d = 0.70, 95% CI [0.41, 0.99]), lower past costs (d = 0.59, 95% CI [0.16, 1.02]), for the ingroup (d = 0.52, 95% CI [0.47, 0.58]), for having some diversification between charities (d = 0.63, 95% CI [0.47, 0.78] for single projects; d = 1.18, 95% CI [1.00, 1.36] for several projects versus one) and against forced charity (d = 0.29, 95% CI [0.21, 0.37]; nominally replicated, but has caveats regarding validity); as at least four of our five hypotheses were found to replicate, we conclude this as being a successful replication. Extending the replication, we found support for an unexpected preference for anonymity on donation allocation (opposite to our predictions; d = 0.54, 95% CI [0.46, 0.61]), and support for a preference towards paid-for overhead costs on donation allocation (d = 0.60, 95% CI [0.52, 0.68]). We discuss the implications and validity of these findings. All materials, data and code were made available on: https://doi.org/10.17605/OSF.IO/BEP78. This registered report has been officially endorsed by Peer Community in Registered Reports: https://doi.org/10.24072/pci.rr.100775.